Internalisasi Adab Shalat di Era Digital: Strategi Pendidikan Akhlak untuk Generasi Milenial dan Z - Mutia Hasanah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
The development of digital technology has brought major changes in the behavior of the millennial and Z generations, including in the religious aspect. This article examines the strategy of internalizing prayer etiquette in the digital era as part of moral education. This study uses a qualitative approach through a literature study of literature on prayer etiquette, the character of the digital generation, and appropriate learning methods. The results of the study indicate that internalization of prayer etiquette among the digital generation must be carried out wisely through the use of digital media, strengthening the role of families and educational institutions, and integrating spiritual values ​​into everyday life. Education on prayer etiquette not only teaches the procedures for worship, but also forms character, such as awareness, solemnity, and discipline. Therefore, a contextual and creative approach is needed so that prayer values ​​can be embedded in the lives of the millennial and Z generations.